2011
DOI: 10.1002/cncr.26206
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic radiation therapy improves the overall survival of patients with extensive-stage small cell lung cancer with distant metastasis

Abstract: BACKGROUND:The authors conducted a retrospective study to evaluate the effects of thoracic radiation therapy (TRT) for patients with extensive-stage small cell lung cancer (ED-SCLC). METHODS: Between January 2003 and December 2006, the records of 119 patients who were diagnosed with ED-SCLC (all with distant metastasis [M1]) were included in the study. Sixty patients received chemotherapy (ChT) and TRT (ChT/TRT), and 59 patients received ChT alone. The ChT regimens consisted of either carboplatin and etoposide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 16 publications
9
65
2
1
Order By: Relevance
“…The optimal dose of TRT is uncertain. Higher doses of TRT appear to be associated with a high risk of esophagitis [16], and this is in keeping with a previous meta-analysis indicating that in non-small cell lung cancer, high-dose metrics (such as the volume of esophagus receiving 60 Gy) are the best predictors of esophagitis risk [20]. Although higher TRT doses may be associated with increased toxicity risk, benefits of such an TRT dose escalation would be ideally assessed in the context of a randomized trial.…”
Section: Page 16mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal dose of TRT is uncertain. Higher doses of TRT appear to be associated with a high risk of esophagitis [16], and this is in keeping with a previous meta-analysis indicating that in non-small cell lung cancer, high-dose metrics (such as the volume of esophagus receiving 60 Gy) are the best predictors of esophagitis risk [20]. Although higher TRT doses may be associated with increased toxicity risk, benefits of such an TRT dose escalation would be ideally assessed in the context of a randomized trial.…”
Section: Page 16mentioning
confidence: 99%
“…TRT doses ranged from 40 to 60 Gy. On multivariable analysis, the use of TRT was associated with improved OS (HR 0.66, p=0.032), at the expense of higher rates of pneumonitis (8% grade 2-5, with one death), esophagitis (22% grade 2-3), and leukopenia[16].…”
mentioning
confidence: 99%
“…A single-institution randomized trial (67) demonstrated an improvement in both local control and OS in patients with a complete distant response and at least partial local response to chemotherapy who received chemotherapy with concurrent thoracic radiotherapy and PCI versus continued chemotherapy and PCI. A single-arm phase II trial (68) and retrospective series also demonstrated an improvement in local disease control with thoracic radiotherapy in carefully selected populations of patients with limited extra-thoracic disease burden (69,70). The CREST Trial/NTR1527 (71) randomized 498 patients with ES-SCLC and response to chemotherapy to thoracic radiotherapy to 30 Gy in 10 fractions and PCI versus PCI alone.…”
Section: Extensive Stage Sclc: Radiation Therapymentioning
confidence: 99%
“…Radiotherapy has a well-established and indispensable role in the treatment of small cell lung cancer (Zhu et al 2011). However, radiation-induced lung injury (RILI) is a major adverse effect associated with radiotherapy for lung cancer, limiting the therapeutic dose of radiation that can be administered.…”
Section: Introductionmentioning
confidence: 99%